Nekatera stališča strokovnih delavcev do agilnosti njihovega vzgojno-izobraževalnega zavoda - Cencič, Majda (Revija za elementarno izobraževanje, 2023)
Agility as a special way of thinking and acting was created by programmers and has spread to the pedagogical field. We are presenting the results of a survey among 184 professionals from various Slovenian educational institutions (EI) for the purpose of determining their attitudes towards the agility of EI. The results show that respondents agree the most with positive actions, positive emotions and care for children. They are most indecisive about simplifying issues and problems and highlighting mistakes. Based on multivariate hierarchic cluster analysis, we determined three clusters that, according to our research, define agile EI. We named them as follows: the individual and the operation of EI, positive mindset and adequate communication. All clusters relate to human resources and confirm the statement that the greatest challenge is to achieve change in people.
Keywords: agility; agilnost; attitudes; changes; educational institution; professionals; spremembe; stališča spremembe; strokovni delavci; vzgojno-izobraževalni zavod